The Histone Acetyltransferase MOF Regulates SIRT1 Expression to Suppress Renal Cell Carcinoma Progression - Guo, Renbo; Liang, Yiran; Zou, Benkui; Li, Danyang; Wu, Zhen; Xie, Fei; Zhang, Xu; Li, Xiangzhi (Frontiers in Oncology, 2022)
Background: Renal cell carcinoma (RCC) is one of the most common and lethal human urological malignancies around the world. Although many advancements in diagnostic and therapeutic strategies have been acquired, the prognosis of patients with metastatic RCC was poor. Thus, there is an urgent need to understand the molecular mechanism of RCC Methods: The quantitative real-time PCR (qRT-PCR) was used to detect the RNA expression of MOF in human RCC tissues and cell lines. The protein expression of MOF was analyzed with immunohistochemistry (IHC) and Western blot. To understand the regulatory mechanism of MOF in liver cancer, ChIP-qPCR assay and dual-luciferase assay were performed. Moreover, a series of in vivo and in vitro experiments were conducted to evaluate the effect of MOF on renal cell carcinoma progression. Results: In the present study, we found that Males absent on the first (MOF), a histone acetyltransferase involved in transcription activation, was significantly decreased in both RCC tissues and RCC cells compared to normal tissues and non-cancer cells. Moreover, MOF downregulation was associated with advanced histological grade, pathologic stage and distant metastasis of RCC patients. Ectopic expression of MOF could significantly attenuate cell proliferation and promote cell apoptosis. Besides, MOF overexpression also suppressed migration of RCC cells through inhibiting epithelial-mesenchymal transition (EMT). Importantly, the inhibition of tumor growth by MOF was further confirmed by in vivo studies. Mechanism dissection revealed that MOF could transcriptionally upregulate the expression of SIRT1, leading to attenuated STAT3 signaling, which was involved in cell proliferation and migration. Moreover, SIRT1 knockdown could restore the biological function induced by MOF overexpression. Conclusions: Our findings indicated that MOF serves as a tumor suppressor via regulation of SIRT1 in the development and progression of RCC, and MOF might be a potent biomarker for diagnosis and prognosis prediction of RCC patients.